Metode Penilaian Akuntansi Agrikultural Berdasarkan IAS 41: Implementasi Fair Value Accounting - Anang Subardjo (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2011)
Agricultural activity is the management by an entity of the biologicaltransformation of biological assets for sale, into agricultual produce or intoadditional biological assets. Biological transformation comprises the processes ofgrowth, degeneratin, production, and procreation that cause qualitative orquantitave changes in biological asset.IAS 41 prescribes, among other things, the accounting treatment for biologicalassets during the period of growth, degeneration, production, and procreation,and for the initial measurement of agricultural produce at the point of harvest.Measurment and valuation in IAS 41 is consistent with a systematic shif in thedominant measurement paradigm away from traditional historical costaccounting model. Implementing Fair Value Accounting proponents point to theenhanced decision usefulness and transparency of fair value informationattributable to its timely reflection of current market conditions.